The Substantion of the Success of the Baltic States in the Process of Transaction to the Market Economy - Visokavičienė, Birutė; Barevičiūtė, Simona (Ekonomika, 2002)
The paper assesses the economic transition experience of the three Baltic countries - Lithuania, Latvia and Estonia - the first among the successor states of the former Soviet Union to liberalize and stabilize their economies. The paper investigates the extent to which progress in transition reflects favorable initial conditions in the Baltic States versus implementation of stable macroeconomic policies and ongoing structural reform. The paper argues that the transition process from central planned to market economy in the Baltic States was successful and that convergence even if difficult to gain but realistic, with the prospect of EU membership providing an added incentive to continue structural reforms.